2021
DOI: 10.2147/nss.s344842
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‑Specific Regional Homogeneity Alterations and Cognitive Function in Obstructive Sleep Apnea Before and After Short-Term Continuous Positive Airway Pressure Treatment

Abstract: Purpose Previous studies have demonstrated abnormal local spontaneous brain activity in the conventional frequency bands (0.01–0.08 Hz) in obstructive sleep apnea (OSA). However, it is not clear whether these abnormalities are associated with the specific frequency band of low-frequency oscillations or whether it can be improved with a continuous positive airway pressure (CPAP) treatment. This study aimed to investigate the regional homogeneity (ReHo) in specific frequency at baseline (pre-CPAP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…45 Additionally, another study and our previous study reported that patients with OSA showed decreased ReHo in the superior frontal gyrus that was correlated with cognitive impairment, which partially overlaps with our findings. 20,46 Similar to these studies, we found that the PerAF values in the left superior frontal gyrus were positively correlated with the MoCA scores in orientation, suggesting that OSA-induced functional abnormalities in the left superior frontal gyrus may be associated with abnormalities in the DMN or other cognitive networks, and the exact association is yet to be further confirmed.…”
Section: Difference In Peraf Between Patients With Osa and Hcssupporting
confidence: 80%
See 2 more Smart Citations
“…45 Additionally, another study and our previous study reported that patients with OSA showed decreased ReHo in the superior frontal gyrus that was correlated with cognitive impairment, which partially overlaps with our findings. 20,46 Similar to these studies, we found that the PerAF values in the left superior frontal gyrus were positively correlated with the MoCA scores in orientation, suggesting that OSA-induced functional abnormalities in the left superior frontal gyrus may be associated with abnormalities in the DMN or other cognitive networks, and the exact association is yet to be further confirmed.…”
Section: Difference In Peraf Between Patients With Osa and Hcssupporting
confidence: 80%
“…38,39 However, some studies have suggested that changes in resting-state brain activity in OSA patients are caused by OSA itself rather than obesity. 17,20 Nevertheless, in this study we included BMI as a covariate to mitigate its effect, and thus, we hypothesized that although there was a difference in BMI between OSA patients and healthy controls, this change was caused by OSA rather than obesity. The present study showed that patients with OSA had higher ESS scores and lower stage 3 + 4 sleep and REM sleep, indicating that these patients are more likely to experience daytime sleepiness due to poor sleep efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al ( 46 ) found that OSA showed decreased network integration connectivity in the cerebellum, which was susceptible to hypoxia or ischemia. After long-term CPAP treatment, patients with OSA may have increased cerebellar volume ( 47 , 48 ). In our study, even one-night CPAP treatment can reverse the brain function of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that after 1 month of CPAP treatment, spontaneous brain activity in the bilateral posterior cerebellar lobe, right superior temporal gyrus, left anterior central gyrus, and other brain regions was reversed, which was related to cognitive function and drowsiness. Such reversible spontaneous brain activity is related to the adaptive compensation of OSA ( 13 ). However, few studies were conducted on whether WM structure is reversed after CPAP therapy.…”
Section: Introductionmentioning
confidence: 99%